Intercultural Analysis in Managing Employee Interaction: Case Study In Pt Semen Indonesia At Padang (Journal of Business and Management, 2022)
Culture is one of the most important aspects of a business and an organization, especially in today's world. There are many factors that influence the adaptation to two different cultures, particularly in Indonesia, where there are significant cultural differences. This can sometimes lead to how to interact in understanding culture and also characteristics. Because of one's cultural background Communication, negotiation, conflict, cross-cultural and interpersonal interactions are all significant aspects of adaptability and intercultural interaction patterns that must be considered in the fusion of one culture with another. This study focuses on a culture, specifically Minangkabau culture, which contains customs and culture that are dense with many manners that must be followed, and how people from diverse cultural backgrounds can understand it To adapt to Minangkabau culture at a company where the majority of employees have Minangkabau cultural origins, as well as how to establish a pattern of interaction inside the company To deepen and obtain the correct viewpoint of employee interaction on Minangkabau culture within a firm, the researcher focuses on collecting data using qualitative methods and analyzing that perspective in order to develop the correct employee interaction in a company. This study focuses on PT Semen Padang, one of the subsidiaries of the Semen Indonesia Group, with a majority of Minangkabau employees, and how they interact at work with enterprises that have a dominating culture.